Come vivere per godersi la vecchiaia; analisi della conversazione di Socrate e Cefalo (Pl. Rep. 328b-331d) - Głodowska, Anna (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2009)
The dialogue between Socrates and Cephalus is an introduction to the deliberations on human life which are elaborated in the further books of Plato’s Republic. Socrates talks with Polemarchus’s father about old age, the influence of wealth on human life and about justice. Cephalus is not a philosopher but he possesses knowledge which springs from his life experience. He becomes resigned to his fate, accepts his limitations connected with his old age and in his life he is driven by simple rules of justice – not to hurt people and to make offerings to the gods.
How to live to enjoy the old age? The analysis of the dialogue between Socrates and Cephalus (Rep. 328b-331d)
Keywords: Plato; old age; wealth; justice; acceptance of one’s fate